Metabolic responses to the acute ingestion of two commercially available carbonated beverages: A pilot study - Mendel Ron W; Hofheins Jennifer E (Taylor & Francis Group, 2007)
Abstract Background The purpose of this placebo-controlled, double-blind cross-over study was to compare the effects of two commercially available soft drinks on metabolic rate. Methods After giving informed consent, twenty healthy men and women were randomly assigned to ingest 12 ounces of Celsius™ and, on a separate day, 12 ounces of Diet Coke®. All subjects completed both trials using a randomized, counterbalanced design. Metabolic rate (via indirect calorimetry) and substrate oxidation (via respiratory exchange ratio) were measured at baseline (pre-ingestion) and at the end of each hour for 3 hours post-ingestion. Results Two-way ANOVA revealed a significant interaction (p < 0.001) between trials in metabolic rate. Scheffe post-hoc testing indicated that metabolic rate increased by 13.8% (+ 0.6 L/min, p < 0.001) 1 hr post, 14.4% (+0.63 L/min, p < 0.001) 2 hr post, and 8.5% (+0.37 L/min, p < 0.004) 3 hr post Celsius™ ingestion. In contrast, small (~4-6%) but statistically insignificant increases in metabolic rate were noted following Diet Coke® ingestion. No differences in respiratory exchange ratio were noted between trials. Conclusion These preliminary findings indicate Celsius™ has thermogenic properties when ingested acutely. The effects of repeated, chronic ingestion of Celsius™ on body composition are unknown at this time.